2002
DOI: 10.1002/glia.10079
|View full text |Cite
|
Sign up to set email alerts
|

RANTES stimulates inflammatory cascades and receptor modulation in murine astrocytes

Abstract: Cultured mouse astrocytes respond to the CC chemokine RANTES by production of chemokine and cytokine transcripts. Stimulation of astrocytes with 1 nM RANTES or 3-10 nM of the structurally related chemokines (eotaxin, macrophage inflammatory protein-1alpha and -beta [MIP-1alpha, MIP-1beta]) induced transcripts for KC, monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-alpha), MIP-1alpha, MIP-2, and RANTES in a chemokine and cell-specific fashion. Synthesis of chemokine (KC and MCP-1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 61 publications
(55 reference statements)
2
47
2
Order By: Relevance
“…The results suggested that CCL2 suppressed IL-12 and augmented TGF-␤ expression in GALT-derived APCs after Ag feeding. Regulation of CCL2 by CCL5 (RANTES) has been demonstrated in astrocyte cultures (24). In the present study, we found that CCR5, the receptor for CCL3 (MIP-1␣), CCL4 (MIP-1␤), and CCL5, is essential to the induction of oral tolerance, and that the lack of oral tolerance seen in CCR5 Ϫ/Ϫ mice is related to CCL5 regulation of CCL2 expression.…”
supporting
confidence: 47%
“…The results suggested that CCL2 suppressed IL-12 and augmented TGF-␤ expression in GALT-derived APCs after Ag feeding. Regulation of CCL2 by CCL5 (RANTES) has been demonstrated in astrocyte cultures (24). In the present study, we found that CCR5, the receptor for CCL3 (MIP-1␣), CCL4 (MIP-1␤), and CCL5, is essential to the induction of oral tolerance, and that the lack of oral tolerance seen in CCR5 Ϫ/Ϫ mice is related to CCL5 regulation of CCL2 expression.…”
supporting
confidence: 47%
“…Expression of RANTES in astrocytes and endothelial cells is stimulated by inflammatory cytokines like TNF-␣ (Croitoru-Lamoury et al, 2003;Hillyer et al, 2003). Conversely, RANTES can also increase the expression of TNF-␣ from astrocytes (Luo et al, 2002). Here we show that RANTES mRNA and TNF-␣ mRNA and protein were increased in hippocampal tissue were significantly increased when LPS-treated astrocytes were cocultured in the presence of endothelial cells (*p Ͻ 0.05; ***p Ͻ 0.001; ANOVA; n ϭ 6 per group) but this effect was attenuated when LPS-treated astrocytes were cocultured in the presence of endothelial cells that were pretreated with rosiglitazone ( ϩ p Ͻ 0.05; ϩϩ p Ͻ 0.01; ANOVA; n ϭ 6 per group).…”
Section: Discussionmentioning
confidence: 99%
“…The CC chemokines MCP-1 and RANTES, which are major attractants for monocyte/macrophage entry into the CNS and key initiators of proinflammatory cascades (Luo et al, 2002a), have been found in the brain tissue and cerebrospinal fluid of patients with HIV-1 encephalitis and AIDS dementia complex (Kelder et al, 1998;McManus et al, 2000). Although the cytokine array is sensitive and can reportedly detect protein levels as low as 4 pg/ml (compared to 40 pg/ml with ELISA), we did not see increases in TNF-α release at 4 or 12 h. Increases in TNF-α were anticipated because Tat has been previously reported to increase TNF-α expression in astrocytes (Chen et al, 1997) and TNF-α can induce the expression of IL-6 (Norris et al, 1994), MCP-1 (Oh et al, 1999;Luo et al, 2003), and RANTES (Oh et al, 1999;Meeuwsen et al, 2003) in human and/or mouse astrocytes.…”
Section: Discussionmentioning
confidence: 99%